Land‐use change to bioenergy: grassland to short rotation coppice willow has an improved carbon balance. Issue 2 (24th April 2016) - Harris, Zoe M.; Alberti, Giorgio; Viger, Maud; Jenkins, Joe R.; Rowe, Rebecca; McNamara, Niall P.; Taylor, Gail
Abstract: The effect of a transition from grassland to second‐generation (2G) bioenergy on soil carbon and greenhouse gas (GHG) balance is uncertain, with limited empirical data on which to validate landscape‐scale models, sustainability criteria and energy policies. Here, we quantified soil carbon, soil GHG emissions and whole ecosystem carbon balance for short rotation coppice (SRC) bioenergy willow and a paired grassland site, both planted at commercial scale. We quantified the carbon balance for a 2‐year period and captured the effects of a commercial harvest in the SRC willow at the end of the first cycle. Soil fluxes of nitrous oxide (N2 O) and methane (CH4 ) did not contribute significantly to the GHG balance of these land uses. Soil respiration was lower in SRC willow (912 ± 42 g C m −2  yr −1 ) than in grassland (1522 ± 39 g C m −2  yr −1 ). Net ecosystem exchange (NEE) reflected this with the grassland a net source of carbon with mean NEE of 119 ± 10 g C m −2  yr −1 and SRC willow a net sink, −620 ± 18 g C m −2  yr −1 . When carbon removed from the ecosystem in harvested products was considered (Net Biome Productivity), SRC willow remained a net sink (221 ± 66 g C m −2  yr −1 ). Despite the SRC willow site being a net sink for carbon, soil carbon stocks (0–30 cm) were higher under the grassland. There was a larger NEE and increase in ecosystem respiration in the SRC willow after harvest; however, the site still remained a carbon sink. Our results indicate that once established, significant carbon savings are likely in SRC willow compared with the minimally managed grassland at this site. Although these observed impacts may be site and management dependent, they provide evidence that land‐use transition to 2G bioenergy has potential to provide a significant improvement on the ecosystem service of climate regulation relative to grassland systems.